PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SEKOLAH DASAR KOTA SAWAHLUNTO - Vemas, Ayatsi; Arwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the lack of information technology-based Student Worksheets (LKPD) utilization in Pancasila Education learning in elementary schools. The purpose of this study was to develop an Electronic LKPD (E-LKPD) using the Liveworksheet platform that is valid, practical, and effective on the topic of Social and Cultural Diversity for Grade IV students. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Trial subjects consisted of 5 Grade IV students from SDN 27 Talago Gunung, while research subjects included 7 Grade IV students from SDN 12 Sapan. Results showed: (1) material validity 83.3% (very valid); (2) language validity 100% (very valid); (3) media validity 97% (very valid); (4) teacher practicality 100% (very practical); (5) student practicality 100% (very practical); and (6) effectiveness 100% (very effective). Therefore, Liveworksheet-based E-LKPD is proven valid, practical, and effective as a Pancasila Education learning medium in Grade IV elementary school.